History of toxicology at the Technical University of Munich (TUM) - Helmut Greim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Toxicology at the TUM is mainly associated with the Faculty of Medicine at the Klinikum rechts der Isar (MRI). The Department of Clinical Toxicology has been founded in 1963. Max von Clarmann, the head, focused his activities on the treatment of intoxications and the development of analytical methods and established a poison information center. His successors, Thomas Zielker and Florian Eyer, further developed this department to an internationally renown institution. In 1967, the MRI became the TUM faculty of medicine with its Institute of Pharmacology and Toxicology. The director Melchior Reiter, formerly Institute of Pharmacology of the Ludwig Maximilians University (LMU), in 1970 initiated the foundation of the Department of Toxicology at the Gesellschaft für Strahlen- und Umweltforschung (GSF) with the director Gerhard Lange. The research focused on the neurotoxic effects of heavy metals and the metabolism and hepatoxicity of persistent chemicals. After Lange’s unexpected death in 1973, he was succeeded in 1975 by Helmut Greim from the University of Tübingen. The now Institute of Toxicology rapidly expanded developing and standardizing in vitro test methods, investigating the mechanism of carcinogens and mutagens and heavy metal toxicity. Training courses in the 15 major areas of toxicology have been organized at the GSF and competent centers in Germany. In 1987, Greim became the director of the newly founded Institute of Toxicology and Environmental Hygiene of the TUM, with expanded research and teaching activities, especially in toxicology at the faculties of Chemistry of the TUM and LMU, which thereafter became mandatory for students of chemistry at German universities.